2020
DOI: 10.1002/mus.27138
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative peripheral nerve interface free muscle graft mass and function

Abstract: Background Regenerative peripheral nerve interfaces (RPNIs) transduce neural signals to provide high‐fidelity control of neuroprosthetic devices. Traditionally, rat RPNIs are constructed with ~150 mg of free skeletal muscle grafts. It is unknown whether larger free muscle grafts allow RPNIs to transduce greater signal. Methods RPNIs were constructed by securing skeletal muscle grafts of various masses (150, 300, 600, or 1200 mg) to the divided peroneal nerve. In the control group, the peroneal nerve was transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Previous work has shown that in rodent models, smaller muscle grafts are most successful as the central zones of these grafts and are more likely to be replaced by regenerating fibers. 11 , 19 Conversely, since VDMTs are perfused by a vascular pedicle, they can heal without the same degree of ischemia-induced fibrosis and do not have the same size limitations as RPNIs. The dimensions of a given VDMT are contingent on the orientation and amount of perfusion provided by its vascular pedicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that in rodent models, smaller muscle grafts are most successful as the central zones of these grafts and are more likely to be replaced by regenerating fibers. 11 , 19 Conversely, since VDMTs are perfused by a vascular pedicle, they can heal without the same degree of ischemia-induced fibrosis and do not have the same size limitations as RPNIs. The dimensions of a given VDMT are contingent on the orientation and amount of perfusion provided by its vascular pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…However, this process has size constraints, as RPNIs that are too large to be maintained by diffusion will undergo central necrosis. 11 , 12 All RPNIs, regardless of size, will undergo some degree of fibrosis and tissue resorption during the healing process. A wound bed that is compromised by radiation or infection also poses the risk of poor graft take.…”
mentioning
confidence: 99%
“…Additionally, the basic science regarding graft survival and reinnervation has been performed on animal models, thus far necessitating further investigation for confirmation in humans. 88 An initial study in a rat model demonstrated that smaller grafts perform better. 89 Larger grafts lose muscle mass in a process consistent with our theory that the portion of the graft receiving plasma imbibition and inosculation will vascularize, with the rest simply sloughing off.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used the vastus lateralis as the autologous donor muscle (Vu et al, 2020b ), though future work may explore other options. Smaller grafts have demonstrated better signal production and tissue viability compared with larger grafts in rat models (Hu et al, 2021 ). Current research is underway to determine optimal size, location, and number of RPNIs that can be used.…”
Section: Surgical Techniquesmentioning
confidence: 99%